Strategi Inovatif Agrowisata Berbasis Komunitas Di Sentra Bawang Merah, Kecamatan Rejoso, Kabupaten Nganjuk - Ezheqiel, Ellyzha Maia; Ahmad Dzaki As Sajjad; Rivandi Pranandita Putra; I Komang Astina (Jurnal Geografi, Edukasi dan Lingkungan (JGEL), 2025)
Nganjuk Regency, as the primary center of shallot production in East Java, holds significant potential for the development of community-based agrotourism. This study aims to analyze the agrotourism potential in Kampung Bawang Merah, Rejoso District, to formulate management strategies involving active community participation, and to examine the economic, social, and educational impacts of its development. This research employs a descriptive qualitative approach supported by quantitative data in the form of spatial analysis of shallot production from 2016 to 2024 using ArcGIS software. The analysis was carried out through thematic mapping to identify areas with high agrotourism potential based on production data. The findings indicate that Rejoso District possesses comparative advantages, including fertile land quality, well-established irrigation infrastructure, and high shallot production. The proposed strategies include product diversification (such as shallot flour and rainbow crackers), community training to enhance technical and entrepreneurial skills, digital marketing through e-commerce platforms, and the development of tourism infrastructure, including educational galleries and souvenir outlets. The study concludes that the development of community-based agrotourism can increase household income, create employment opportunities, preserve traditional agricultural culture, and positively contribute to the regional economy. Recommendations emphasize the importance of collaboration between the government, local communities, and the private sector to ensure program sustainability and position Kampung Bawang Merah as a leading educational agrotourism destination in East Java.